Evaluation of the Insulin-like Growth Factor Receptor Pathway in Patients with Advanced Breast Cancer Treated with Trastuzumab - CHRISTODOULOU, CHRISTOS (Cancer Genomics Proteomics, 2018)
Background: Trastuzumab is a monoclonal antibody against HER2-positive breast cancer. Despite improving the natural history of the disease, there is a number of patients who are resistant to it, whereas all patients will eventually develop resistance and disease will progress. Inconsistent preclinical data show that the IGF-R pathway may contribute to either de novo or acquired resistance to trastuzumab. Materials and Methods: In total, 227 trastuzumab-treated metastatic breast cancer patients were evaluated for IGF-1, IGF-1R, GLP-1R, Akt1, Akt2 Akt3 mRNA expression, and IGF-1Rα, IGF-1Rβ, IGF-2R protein expression. Results: Only 139 patients were truly HER2-positive by central assessment. Among HER2-positive patients, high Akt2 and GLP-1R mRNA expression showed a trend towards higher and lower risk of progression, respectively (HR=1.83, 95%CI=0.90-3.72, p=0.094 and HR=0.62, 95%CI=0.36-1.06, p=0.079), while high Akt1 and GLP-1R mRNA expression presented a trend towards unfavorable survival (HR=1.67, 95%CI=0.93-2.99, p=0.086 and HR=1.67, 95%CI=0.94-2.96, p=0.080). Among HER2-negative patients, high GLP-1R mRNA expression and negative stromal IGF-1Rβ protein expression showed a trend towards worse survival (HR=2.31, 95%CI=0.87-6.13, p=0.094 and HR=2.03, 95%CI=0.94-4.35, p=0.071, respectively). In the multivariate analyses, HER2-positive patients with high Akt1 and GLP-1R mRNA expression had a worse survival (HR=1.86, 95%CI=1.01-3.43, p=0.045 and HR=1.83, 95%CI=0.99-3.41, p=0.055, respectively). Conclusion: This study revealed a crosstalk between the IGF-R pathway and HER2. There was evidence that high Akt1 and GLP-1R mRNA expression might affect survival among HER2-positive metastatic breast cancer patients treated with trastuzumab.